An Analysis of Heat Flows in the Combustion Engine of a Ship Non-Conventional Energetic System - Hlavna, Vladimir; Sojcak, Dusan (Communications - Scientific letters of the University of Zilina, 2005)
The paper describes a possibility of implementation of a non-conventional energetic system for ships. The described system is a source of heat at three levels, cool, refined electric energy and mechanical energy. Individual secondary energies are acquired by means of transformation of primary chemically bound energy in fuel. Primary energy is transformed by means of a combustion engine used as a driving unit of ships designed for transportation of passengers and goods. Mechanical energy can be used to drive a ship and its equipment. Exergy as a source of heat and cool for technological equipment of a ship. The implementation of a non-conventional system of a ship offers more possibilities for effective usage and increases energetic evaluation of the combustion engine in this means of transport. The paper analyses heat flows in the non-conventional cooling circuit of the combustion engine of a ship energetic system.